Information Technology Utilization and Internal Control Accounting for the Value of Financial Reporting Information - Siti Rahmayuni; Anwar Arifin Pinem (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: of this research is to know the effect of utilization of information technology and internal control of accounting for the value of financial reporting information Design/methodology/approach: quantitative methods using multiple linear regression methods. Findings: Utilization of Information Technology, internal accounting controls have a significant effect on the value of financial reporting information at the Center for Research and Development of Natural Resources Conservation Technology, East Kalimantan. Research limitations/implications: Utilization of Information Technology, internal accounting controls. Practical implications: Results show that from the 2 hypotheses proposed. Originality/value: This paper is original. Paper type: Research paper